Aplikasi Omni-channel untuk Pengaturan Multi-channel Order Management di Toko Kyuuden - Katherine Putri Sutjiadi; Yulia Yulia; Krisna Wahyudi (Universitas Kristen Petra, 2022)
Kyuuden store is an online store that provides variety of electronics products especially games related. Kyuuden store sold in marketplace platform such as Shopee, Tokopedia, Bukalapak, OLX, and Blibli. The store currently storage or collecting data manually with Ms. Excel while there are a lot of data to manage which made the data management much more difficult. Not just managing data, Kyuuden store make sales in more than one marketplace platform which makes it also difficult and wasting more time to managing it. Based on those problems, it needed an omni-channel application that integrates data from multiple channels and can manage computerized all the business activity data. The integrated channels are offline channel, Shopee, and Tokopedia. This application programmed with PHP framework Codeigniter 3 and database phpmyadmin MySQL. This application has two access group such as owner and administrator. Final result of this research and application is that this application can integrating data, managing data, dan synchronizing data within all channels either online or offline. From the questionnaire result with the respondent, 75% user response that overall application could help the business process of Kyuuden store.